1999
DOI: 10.1093/oxfordjournals.pcp.a029555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Horizontal Clinorotation on the Root System Development and on Lipid Breakdown in Rapeseed (Brassica napus) Seedlings

Abstract: Seedlings of Brassica napus were cultivated on a slowly rotating clinostat (1 rpm) or in the vertical control for 5 d. The root growth, the cotyledonary reserves and the transport of 14C-labeled sucrose from cotyledons to root system were studied in both cultural conditions. The biomass (fresh weight) of the root system was 35% higher in the horizontally clinorotated seedlings than in the controls. This increase was correlated with a greater degradation of reserve lipids and faster accumulation of sucrose in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…In the two experiments, samples grown in space were enriched in earlier phases with respect to 1g controls, and the authors concluded that the cell cycle was slowed down in microgravity. However, this conclusion does not take into account a possible different effect of microgravity depending on the time of exposure and/or on the phase of development of the plant or seedling (Claassen and Spooner, 1994;Aarrouf et al, 1999). In fact, this time of growth under microgravity conditions was quite different in these experiments (28-29 h) and in the experiment reported in the present paper (4 d).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In the two experiments, samples grown in space were enriched in earlier phases with respect to 1g controls, and the authors concluded that the cell cycle was slowed down in microgravity. However, this conclusion does not take into account a possible different effect of microgravity depending on the time of exposure and/or on the phase of development of the plant or seedling (Claassen and Spooner, 1994;Aarrouf et al, 1999). In fact, this time of growth under microgravity conditions was quite different in these experiments (28-29 h) and in the experiment reported in the present paper (4 d).…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, it has been hypothesized that the action of microgravity might depend on the duration of exposure to microgravity and/or on the developmental stage of the plant (Claassen and Spooner, 1994). The hypothesis was confirmed experimentally in clinorotated samples (Aarrouf et al, 1999), but not with real microgravity.…”
Section: Introductionmentioning
confidence: 97%
“…If this is true, our seedlings from large seeds could accumulate more carbohydrate reserves because of their rapid growth. It has been showed [1,19,24,27] that the carbohydrate reserves play an important role in lateral root emergence, and that seedling performance depends on the rapidity of emergence of lateral roots [6,16,37].…”
Section: Discussionmentioning
confidence: 99%
“…The pellet that remained after the soluble sugars were extracted was solubilized in 52% perchloric acid for determination of starch content (McCready et al, 1950). Total soluble sugars and starch were estimated according to the anthrone-sulphuric acid method of McCready et al, (1950), with some modification (Aarrouf et al, 1999). We used 0.2% anthrone in concentrated H2SO4 as the reagent.…”
mentioning
confidence: 99%
“…Spectrophotometric readings were taken at 630 nm, and a standard curve was plotted with 0 to 100 pg of pure glucose. The concentration of starch was determined by multiplying the obtained value by 0.9 for converting the glucose value to starch content (Aarrouf et al, 1999). We adapted the alkaline copper methods of Nelson (1944) and Somogyi (1945) for estimating the amount of reducing sugars, using an arsenomolybdate reagent.…”
mentioning
confidence: 99%